Historical thinking skills of selected public high school students in Metro Manila - Cristobal, Cristina B. (2004)
Empirical studies in the 1980s and 1990s on Filipino children's historical knowledge revealed that public elementary and high school students' sense of history was weak. This study sought to make further investigations, focusing this time on children's thinking skills in history. The method of investigation was both qualitative and quantitative, the latter being of the correlational type. 57 high school students from 2 public high schools in Metro Manila participated in the study. Findings revealed that the participants processed historical thinking skills at various levels of thinking, from the most simple to the most complex. These findings showed the viability of teaching historical thinking skills among our students. However, the issue of social context of the learner, specifically that of school type, needs to be addressed.
Thesis (Ph.D. Social Studies Education)--University of the Philippines, Diliman.
Keywords: History -- Study and teaching (Secondary) -- Philippines -- Manila Metropolitan Area; Critical thinking -- Study and teaching (Secondary) -- Philippines -- Manila Metropolitan Area